The development of a core outcome set for evaluating and enhancing palliative sedation in clinical research and practice: The COSEDATION study protocol - Lenzo Robijn; Indra Albrecht; Joni Gilissen; Peter Pype; Jeroen Hasselaar; Luc Deliens; Kenneth Chambaere (Palliative Care and Social Practice)
Background: The practice of palliative sedation (PS) in end-of-life care has generated significant debate due to concerns about improper application and communication issues. Previous efforts to assess and enhance the practice have often focused on single outcomes, resulting in incomplete evaluations. There is currently no consensus on the core outcomes needed to assess PS effectively. Aim: This study aims to develop a core outcome set (COS) for PS in end-of-life care to enable comprehensive evaluation and improve clinical practice. Design: The study follows the four-stage Core Outcome Measures in Effectiveness Trials (COMET) initiative approach to develop the set of core outcomes. Methods and analysis: First, we will conduct a scoping review to identify potentially relevant outcomes reported in existing peer-reviewed and gray literature. Second, we will employ qualitative methods to explore outcomes valued by patients, their proxies, and healthcare professionals. Third, experts, including researchers, healthcare providers and bereaved relatives, and patient advocates will assess the importance of these outcomes through a Delphi study. Finally, a consensus meeting with stakeholder representatives will refine the COS. Concurrently, measurement instruments for these core outcomes will be identified. Ethics: Ethical clearance was obtained by the Ghent University Hospital Ethics Committee for the whole study (ONZ-2023-0050). Discussion: This study is crucial for establishing a gold-standard measurement instrument to evaluate the multifaceted practice of PS in all its complexity. Providing a standardized set of outcomes will facilitate the design and evaluation of clinical trials, support effective quality improvement initiatives, and inform evidence-based decision-making in healthcare. Engaging all key stakeholders, including dying persons and their families, significantly improving patient care. Furthermore, internationally validated, clinically relevant endpoints will further strengthen research impact and promote consistent, high-quality PS practices worldwide.